Introduction to green chemistry - Andraos, John, 1964-; Matlock, Albert S. (CRC Press, Taylor and Francis, 2022)
"The book covers traditional green chemistry topics, including catalysis, benign solvents, and alternative feedstocks. It also discusses relevant but less frequently covered topics with chapters such as Chemistry of Longer Wear and Population and the Environment. This coverage highlights the importance of chemistry to everyday life and demonstrates the benefits the expanded exploitation of green chemistry can have for society"- Resumé vydavatel